Long noncoding RNA LINC00346 promotes glioma cell migration, invasion and proliferation by up‐regulating ROCK1 - Chen, Xin (J Cell Mol Med, 2020)
Long noncoding RNAs have key roles in glioma progression. However, the function and mechanisms of action of the long noncoding RNA, LINC00346, in glioma remain unclear. In our study, we observed that LINC00346 levels were increased in glioma tissue samples, and according to Gene Expression Profiling Interactive Analysis, its levels were related to disease‐free survival and overall survival rates, suggesting that a high level of LINC00346 expression corresponds to a poor prognosis. We next confirmed the high levels of LINC00346 expression in glioma tissues and cell lines and showed that LINC00346 knockdown suppressed glioma cell proliferation, migration and invasion; promoted apoptosis; and delayed tumour growth. Moreover, the oncogenic function of LINC00346 may be explained, in part, by the down‐regulation of miR‐340‐5p and the de‐repression of ROCK1. We showed that LINC00346 may function as a competing endogenous RNA of miR‐340‐5p, thereby de‐repressing ROCK1. This study revealed a new regulatory network in glioma and identified potential therapeutic targets for this cancer.